Soroepidemiologia das hepatites virais B e C nas comunidades ribeirinhas residentes na região do lago da usina hidrelétrica de Tucuruí, estado do Pará - ALMEIDA, Marcella Kelly Costa de (Universidade Federal do Pará, 2013)
Viral hepatitis is a disease caused by different etiologic agents that have in common hepatotropism. Epidemiologically, the relevance of these diseases is due to the wide geographic distribution and the huge number of infected individuals in virtually every country in the world. For this study were 668 randomly selected residents of the islands of Tucuruí dam lake. We collected blood samples for research of serological markers HBsAg, anti-HBc, Anti-HBs and anti-HCV using enzyme immunoassay. Patients with reactive serology for HCV were tested by molecular biology (RT-PCR and RFLP) for detection of viral genotypes. Of the 668 coastal studied, 1.95% were positive for HBsAg, 28% for Anti-HBc Total and 41.91% for anti-HBs. The presence of the marker anti-HBs alone (vaccine response) was observed in 25.75% of the volunteers. The serological marker for hepatitis C was observed in 2.24%, and of these 70% had genotype 1. The results indicate an intermediate level of endemicity in this region for HBV and HCV. In addition to HBV vaccination coverage is low.